2017
DOI: 10.1186/s11671-017-2109-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen treatment temperature on the properties of InGaN/GaN multiple quantum wells

Abstract: InGaN/GaN multiple quantum wells (MQWs) were grown with hydrogen treatment at well/barrier upper interface under different temperatures. Hydrogen treatment temperature greatly affects the characteristics of MQWs. Hydrogen treatment conducted at 850 °C improves surface and interface qualities of MQWs, as well as significantly enhances room temperature photoluminescence (PL) intensity. In contrast, the sample with hydrogen treatment at 730 °C shows no improvement, as compared with the reference sample without hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Furthermore, our argument that the interface roughness plays a key role for optical properties of these systems might also be related to the experimentally reported enhancement of the PL intensity of InGaN/GaN QWs after reduction of the surface roughness via Hydrogen treatment during growth. 62 In addition to these device related aspects, our above presented results indicate also potential changes in the fundamental physical properties of the radiative recombination dynamics of InGaN/GaN QWs with varying well width. Here, we find for instance that for some configurations the recombination process may be considered as being driven by exciton localization effects (cf.…”
Section: Comparison With Experiments and Consequencesmentioning
confidence: 70%
“…Furthermore, our argument that the interface roughness plays a key role for optical properties of these systems might also be related to the experimentally reported enhancement of the PL intensity of InGaN/GaN QWs after reduction of the surface roughness via Hydrogen treatment during growth. 62 In addition to these device related aspects, our above presented results indicate also potential changes in the fundamental physical properties of the radiative recombination dynamics of InGaN/GaN QWs with varying well width. Here, we find for instance that for some configurations the recombination process may be considered as being driven by exciton localization effects (cf.…”
Section: Comparison With Experiments and Consequencesmentioning
confidence: 70%
“…Considering that the electrons and holes are non-equilibrium distributed in QWs under the condition of electric injection, the high luminous efficiency is closely related to the transported carriers. To further investigate the effect of transported carriers on the luminescence, another sample (Sample B) without hydrogen annealing treatment on the QW layers is prepared, considering that the hydrogen annealing treatment can effectively etch the In-rich layers and improve the interface quality of the MQW [ 25 , 26 ] which can provide more non-equilibrium carriers participated in luminescence.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the dislocation defects generally produce V-shape pits on the QBs [27], in which the carriers are more possible to participate the non-radiative recombination process. With H 2 -treatment on the surface of the quantum wells, the adatom indium in the InGaN epitaxial layer will be removed by the hydrogen atom due to the etching effect [25,28,29], weakening the restriction effect on carriers. As a result, the MQWs of sample A is much better than that of sample B, leading to a higher luminescence efficiency of sample A.…”
Section: Resultsmentioning
confidence: 99%
“…To solve these problems, various growth techniques have been employed to strive for sharp interfaces in the MQW and a homogeneous distribution of indium composition. Growth of barrier layers at a higher temperature [17,18], temperature ramp-up process after the growth of QWs [19,20], the interruption of growth between quantum barriers (QBs) and QWs [21,22], and growth of barriers in hydrogen atmosphere [23,24] are known to be effective for the quality improvement of MQWs. However, in most techniques, the temperature ramp-up process is necessary, which will hinder the indium incorporation and causes thermal degradation of MQWs with higher indium content.…”
Section: Introductionmentioning
confidence: 99%
“…But for the growth of InGaN well layers, researchers found that even a small amount hydrogen will strongly deteriorate the indium incorporation [ 6 , 25 ]. As a result, hydrogen is not widely used in the growth of InGaN epilayers [ 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%